"If I knew what I was doing on Twitter then I would use it more": Twitter experiences and networks of people with traumatic brain injury (TBI). Issue 1 (4th March 2020) - Brunner, Melissa; Palmer, Stuart; Togher, Leanne; Dann, Stephen; Hemsley, Bronwyn
Abstract: Aim: of this study was to examine the Twitter experiences and networks of six adults with cognitive-communication disability after a traumatic brain injury (TBI). Method: Using mixed methods, the study integrated: (a) quantitative analysis of Twitter networks using computational and manual coding of tweets; and (b) narrative analysis of in-depth interviews. Results: Diverse experiences were evident, with two experienced and four novice users of the platform. However, all reported feeling connected and included, and identified both positive and negative experiences in their use of Twitter. Developing a supportive network facilitated higher frequency of tweets and increased feelings of enjoyment and connectedness. All expressed a desire to continue using or learning to use Twitter but novices lacked support from rehabilitation professionals or experienced Twitter users, and relied instead on a "trial and error" approach. Conclusion: Proactive integration of Twitter use during rehabilitation after TBI is warranted to support safe, enjoyable, and meaningful use.